2023
DOI: 10.1088/2053-1591/acb1f8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, enhancement of permeability, and anti-biofouling properties of PEES/nano-silver/PVP mixed-matrix membrane

Abstract: This study investigated the separation of bovine serum albumin using a novel matrix mixed membrane composed of poly vinyl pyrrolidone and poly (phenylene ether ether sulfone)/Nano-silver. The responsive bare and modified PEES/Nano-silver membranes were evaluated using morphology, wettability, XRD and ATR-FTIR. The molecular weight cut-off (MWCO), water content, mean pore radius, porosity, and pure water flux were used to evaluate the presentation of mixed matrix membranes. The outcomes show that the membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…The initial permeability of unmodified membrane was 143 L/(h·m 2 ·bar), which almost doubled to 269 L/(h·m 2 ·bar) when PVP was used in a non-ZnO membrane. This can be explained by the well-known ability of PVP to increase the flux, as was also found in a study by Soundarrajan et al [ 52 ]. The same effect of PVP could be observed in modified dual-layer ZnO membranes where the addition of PVP more than quadrupled the initial clean water flux of the non-PVP membrane (Z2) from 55 to 228 L/(h·m 2 ·bar).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The initial permeability of unmodified membrane was 143 L/(h·m 2 ·bar), which almost doubled to 269 L/(h·m 2 ·bar) when PVP was used in a non-ZnO membrane. This can be explained by the well-known ability of PVP to increase the flux, as was also found in a study by Soundarrajan et al [ 52 ]. The same effect of PVP could be observed in modified dual-layer ZnO membranes where the addition of PVP more than quadrupled the initial clean water flux of the non-PVP membrane (Z2) from 55 to 228 L/(h·m 2 ·bar).…”
Section: Resultssupporting
confidence: 64%
“…N1-unmodified membrane; N2-unmodified membrane with PVP; Z1-single-layer ZnO membrane; Z2-dual-layer ZnO membrane; Z3-dual-layer ZnO membrane with PVP.The initial permeability of unmodified membrane was 143 L/(h•m 2 •bar), which almost doubled to 269 L/(h•m 2 •bar) when PVP was used in a non-ZnO membrane. This can be explained by the well-known ability of PVP to increase the flux, as was also found in a study by Soundarrajan et al[52]. The same effect of PVP could be observed in modified dual-layer ZnO membranes where the addition of PVP more than quadrupled the initial clean water flux of the non-PVP membrane (Z2) from 55 to 228 L/(h•m 2 •bar).Comparison of ZnO membranes with non-ZnO membranes showed that clean water flux decreases once ZnO NPs are implemented.…”
supporting
confidence: 69%